Seismic Analysis of Reinforced Concrete Pier Strengthened by Carbon Fiber Reinforced Polymers - Abass, Sarah Fadhil; Muhammad, Bassman R.; Hasan, Qais A.; Hasan, Qais A. (Al-Nahrain Journal for Engineering Sciences, 2020)
In this vast world after an earthquake lessons are learned; many strategies have been considered in order to achieve a proper seismic strength capacity.The aim of this paper is studying the seismic behavior of a typical reinforced concrete bridge pier in Iraq and implementing a proper technique of strengthening in order to fix any damage that had happened.Structure of a full scale three-dimensional finite element model was used in order to simulate a reinforced concrete pier via the computer software ABAQUS/CAE 2017 using concrete plasticity damage model (CDP).Under the action of Halabja earthquake, which was recorded at city of Halabja in Iraq on 12 November 2017, the behavior of model was traced, analyzed and the resulted damages were managed.The finite element analysis results indicated that the proposed configuration of carbon fiber reinforced polymers laminates substantially increases the lateral load strength and deformation capacity of the bridge pier